Effectiveness of Teaching English for Specific Purposes in LMS Moodle: Lecturers' Perspective - Prasetya, Rizky Eka (Journal of English Language Teaching and Linguistics, 2021)
Learning management systems (LMS) Moodle presents a beneficial arrangement of features that support language learning in the electronic environment. The English lecturers' challenge is to obtain interaction and adaptability with their online classroom. The study is to find the effectiveness of teaching English in Moodle-based.Â  The semi-structured interviews and open-ended questioner were employed to recognize the complete information to the English lecturer's teaching experiences based on Moodle. This study determines that the effective teaching of English Moodle-based depends on both lecturer competences in pedagogy English and lecturer experience in the Moodle system. It covers a complete curriculum with high expectations, composes applicable model content, and constructs it more obtainable, provides specific and culturally applicable instruction, maintains practical approaches to explicit learning strategies, allows learnings to use the first language, prepares vocabulary in various contexts, and develops reading comprehension, and integrates communicative competence abilities. The language learning activities of the Moodle classroom are capable of fulfilling learning practice for complete progression participants with peculiar configuration, management, adjustments, and teaching approach. The English teaching course designer should organize and manage an expected course model of course-related activity, and it applied to the utilization of the syllabus or course information page. The essential aspect of interchangeable communication significantly reshapes language teaching pedagogy in the electronic ecosystem. The effective teaching of English Moodle-based can be achieved with teaching pedagogy's full capabilities and technicality in the Moodle system.